The Association of Drug-Use Characteristics and Active Coping Styles With Positive Affect in Patients With Heroin-Use Disorder and Methamphetamine-Use Disorder During the COVID-19 Pandemic - Wang, Yingying; Zuo, Jinsong; Wang, Long; Wang, Qianjin; Wang, Xin; Yang, Qian; Wu, Hanjing Emily; Goodman, Colin B.; Wang, Dongmei; Liu, Tieqiao; Zhang, Xiangyang (Frontiers in Public Health, 2021)
Background: Positive affect (PA) is crucial for individuals to cope with the current pandemic and buffer the lingering fears after it, especially for patients with substance use disorders (SUDs). The current study aimed to explore PA and its related factors during the COVID-19 pandemic in male patients with heroin use disorder (HUD) and patients with methamphetamine use disorder (MAUD), respectively. Methods: A total of 325 male patients with SUDs (106 with HUD and 219 with MAUD, all were single substance users) in a compulsory rehabilitation center underwent semi-structured interviews during the pandemic. The participants’ demographic information, drug use characteristics, active coping styles (ACS, by Simple Coping Style Questionnaire) and PA (by Positive and Negative Affect Scale) were collected and recorded. Results: There were significant differences between the two groups in age, proportion of full-time workers before the epidemic, duration of drug use, proportion of patients with long-term withdrawal during the epidemic, cravings, ACS, and PA. Correlation and multiple linear regression analysis showed that duration of drug use, ACS, and stable jobs were significant predictive factors for PA in patients with HUD, while long-term withdrawal, ACS, and stable jobs during the epidemic were significant predictive factors for PA in patients with MAUD. Conclusions: Our study demonstrated the factors for PA in patients with HUD and MAUD during the pandemic. The results provided a basis for the comprehensive understanding of the PA of patients with SUDs and the development of targeted treatments.